2016
DOI: 10.1016/j.chom.2016.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-Induced Adhesin-Receptor Interaction Provides a Fitness Advantage to Uropathogenic E. coli during Chronic Infection

Abstract: SUMMARY Uropathogenic E. coli (UPEC) is the dominant cause of urinary tract infections, clinically described as cystitis. UPEC express CUP pili, which are extracellular fibers tipped with adhesins that bind mucosal surfaces of the urinary tract. Here we identify the role of the F9/Yde/Fml pilus for UPEC persistence in the inflamed urothelium. The Fml adhesin FmlH binds galactose β1-3 N-acetylgalactosamine found in core-1 and -2 O-glycans. Deletion of fmlH had no effect on UPEC virulence in an acute mouse model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 60 publications
2
59
0
1
Order By: Relevance
“…10 P-fimbriated UPEC plays an important role in the pathogenesis of ascending UTIs and pyelonephritis 11 and UPEC expressing F9 fimbriae are associated with binding to chronic and inflamed bladder epithelium. 12 Extensive research has been conducted to investigate bioactive components in cranberries that are responsible for the anti-adhesion activity. Previous studies have shown that cranberry polyphenolic compounds such as proanthocyanidins, 13,14 flavonols and their glycosides (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…10 P-fimbriated UPEC plays an important role in the pathogenesis of ascending UTIs and pyelonephritis 11 and UPEC expressing F9 fimbriae are associated with binding to chronic and inflamed bladder epithelium. 12 Extensive research has been conducted to investigate bioactive components in cranberries that are responsible for the anti-adhesion activity. Previous studies have shown that cranberry polyphenolic compounds such as proanthocyanidins, 13,14 flavonols and their glycosides (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A homolog of the type 1 pilus, the F9 pilus, is one of the most common CUP pili in the E. coli pan genome and an important urovirulence factor employed by UPEC for the maintenance of UTI ( 21 , 33 ). Our recent work has demonstrated that UPEC up-regulates the expression of F9 pili in response to bladder inflammation and epithelial remodeling induced upon UPEC infection ( 34 ). These pili display the FimH-like adhesin FmlH, which is capable of binding terminal galactose (Gal), N -acetylgalactosamine (GalNAc), or Thomsen-Friedenreich antigen (TF) [Gal(β1-3)GalNAc(α)].…”
mentioning
confidence: 99%
“…These include both human red blood cell (HRBC) agglutination and epithelial cell binding assays and have primarily focused on the use of uropathogenic P-fimbriated and Type 1 fimbriated E. coli strains (e.g., CFT073, MG1655), though additional E. coli strains have also been used. In vivo, bacteria such as E. coli may express multiple and diverse adhesion phenotypes that provide fitness advantages in specific environments [199,206]. Bacterial-epithelial cell adhesion assays are therefore more representative of the complexity of bacteria-host interactions within in vivo systems than those that depend on specific receptor binding such as bacterial-HRBC anti-agglutination assays [198,199,207].…”
Section: Effects On Bacterial Adhesionmentioning
confidence: 99%